Augmenting Mental Health in Primary Care: A 1-Year Study of Deploying Smartphone Apps in a Multi-site Primary Care/Behavioral Health Integration Program - Hoffman, Liza; Benedetto, Emily; Huang, Hsiang; Grossman, Ellie; Kaluma, Dorosella; Mann, Ziva; Torous, John (Frontiers in Psychiatry, 2019)
Background: Integrating behavioral health (BH) services into primary care is an evidence-based intervention that can increase access to care, improve patient outcomes, and decrease costs. Digital technology, including smartphone apps, has the potential to augment and extend the reach of these integrated behavioral health services through self-management support impacting lifestyle behaviors. To date, the feasibility and acceptability of using mental health mobile apps within an integrated primary care setting has not yet been explored as part of routine clinical care. Objectives: The objectives of this study were to a) test the feasibility of using mental health applications to augment integrated primary care services; b) solicit feedback from patients and providers to guide implementation, and c) develop a mental health apps toolkit for system-wide dissemination. Methods: Cambridge Health Alliance (CHA) is a safety-net healthcare system that includes two community hospitals and 12 Primary Care (PC) clinics serving nearly 150,000 ethnically and socioeconomically diverse patients around Boston. To select and disseminate mental health apps, a four-phase implementation was undertaken: 1) Evaluation of mental health mobile applications 2) Development of an apps toolkit with stakeholder input, 3) Conducting initial pilot at six primary care locations, and 4) Rolling out the app toolkit across 12 primary care sites and conducting one-year follow-up survey. Results: Among BH providers, 75% responded to the follow-up survey and 83% indicated they use apps as part of their clinical care. Anxiety was the most common condition for which app use was recommended by providers, and 42% expressed interest in further developing their knowledge of mental health apps. Among patients, 65% of participants provided feedback; 66% reported the tools to be helpful, especially for managing stress and anxiety. Conclusions: Our findings indicate mental health apps are applicable and relevant to patients within integrated primary care settings in safety-net health systems. Behavioral health providers perceive the clinical value of using these tools as part of patient care, but require training to increase their comfort-level and confidence applying these tools with patients. To increase provider and patient engagement, mobile apps must be accessible, simple, intuitive and directly relevant to patients’ treatment needs.